A method for preparing environmental restoration functional materials from stone mine tailings

By crushing aluminosilicate stone tailings, modifying it with sodium hydroxide, heating, cooling, and treating cyclohexanol and 2-cyclohexen-1-ol, materials with environmental remediation functions were prepared to solve the problem of stone tailings. Effective adsorption of heavy metal elements has been achieved to solve the problems of insufficient mineral utilization and environmental pollution.

CN118634780BActive Publication Date: 2025-01-21中电建路桥集团有限公司 +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410754665.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-12
Publication Date
2025-01-21
Estimated Expiration
2044-06-12

AI Technical Summary

Technical Problem

The insufficient utilization of tailings in stone mines leads to environmental pollution.

Method used

By crushing aluminosilicate stone tailings and mixing it with sodium hydroxide solution, after heating and cooling, cyclohexanol and 2-cyclohexen-1-ol are added to prepare materials with environmental remediation functions. .

Benefits of technology

This method effectively utilizes the silica and alumina in the stone tailings, removes the ash content of the tailings particles, improves its adsorption capacity, can effectively absorb heavy metal elements, and solves the problems of insufficient utilization of stone tailings and environmental pollution. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118634780B_ABST
    Figure CN118634780B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of tailings environmental restoration materials, and in particular to a method for preparing environmental restoration functional materials from tailings of a stone mine, which comprises the following steps: crushing aluminosilicate stone tailings to obtain a rough treated material, the particle size of the rough treated material being no more than 2 mm; mixing the rough treated material with a sodium hydroxide solution and stirring for at least 0.5 h to obtain a first mixture; placing the first mixture in a heating container, heating the heating container from 10 ° C at a heating rate of 5 ° C / min, and maintaining it at a first constant temperature for 1.5~3 h; cooling the first mixture to no more than 25 ° C, adding at least one of 0.1 mol / L of cyclohexanol and 0.1 mol / L of 2-cyclohexene-1-ol, stirring for at least 20 min, and obtaining an environmental restoration material. The present application embodiment provides a method for preparing environmental restoration functional materials from tailings of a stone mine to solve the problem of insufficient utilization of stone tailings in related technologies and easy environmental pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of tailings environmental restoration materials, and in particular to a method for preparing environmental restoration functional materials from stone mine tailings. Background Art

[0002] With the construction of infrastructure and the development of new energy, the demand for building materials and special materials is increasing, which has promoted the demand for mining. After the raw ore enters the concentrator and undergoes crushing, grinding and sorting operations, the useful minerals in the ore are sorted into one or more concentrate products, and the tailings are discharged in the form of slurry. The amount of tailings is large (the yield is usually 80~90%), and a large amount of metal elements will enter the environment during the mining process of metal mines, causing harm to the environment.

[0003] The large-scale mining of metal ores and the use of energy have caused heavy metal pollution to water and soil. The treatment of heavy metal pollution in water and soil is imminent. One way people solve the problem of environmental pollution is to find non-metallic minerals to remove environmental pollutants in order to achieve the purpose of purifying the environment. The so-called non-metallic minerals refer to those minerals that are not mainly used for the extraction of metal elements.

[0004] Stone is one of the most widely used materials in my country. It is widely used in various construction projects, decoration design, public facilities construction, etc. In the process of modernization, the mining of stone and other mining resources has become an inevitable choice for people. The main minerals in stone mines include granite, tuff, sandstone and limestone, and their main components include silicon dioxide and aluminum oxide. At the same time, a large amount of tailings, including dust, waste slag, etc., will be produced during the stone mining process.

[0005] In the related art, the treatment methods of tailings generated by stone mining usually include road paving, building material filling, concrete blocks or filling mine goafs. However, since the waste slag generated by stone tailings is heavy and large in volume, although these methods have achieved secondary utilization, the tailings need to be transported, which invisibly increases the treatment cost, and there is a risk of secondary pollution during transportation. Therefore, there is an urgent need for a method to effectively utilize stone tailings. Summary of the invention

[0006] The embodiment of the present application provides a method for preparing environmental restoration functional materials from stone mine tailings to solve the problem of insufficient utilization of stone tailings in related technologies, which easily causes environmental pollution.

[0007] To achieve the above objectives, the present application provides a method for preparing environmental restoration functional materials from stone mine tailings, which comprises the following steps:

[0008] The aluminum silicate stone tailings are crushed to obtain a rough-processed product of the aluminum silicate stone tailings, wherein the particle size of the rough-processed product is not greater than 2 mm;

[0009] The crude product is mixed with a sodium hydroxide solution and stirred for at least 0.5 h to obtain a first mixture;

[0010] Placing the first mixture in a heating container, heating the heating container from 10° C. at a heating rate of 5° C. / min, and maintaining the first constant temperature for 1.5 to 3 hours;

[0011] The first mixture is cooled to no higher than 25° C., at least one of 0.1 mol / L of cyclohexanol and 0.1 mol / L of 2-cyclohexene-1-ol is added, and stirred for at least 20 minutes to obtain an environmental remediation material.

[0012] Preferably, the concentration of the sodium hydroxide solution is not less than 20%.

[0013] Preferably, the concentration of the sodium hydroxide solution is greater than 40%.

[0014] Preferably, the sodium hydroxide solution is added in excess and the pH value of the first mixture is not less than 7.

[0015] Preferably, the pH value of the first mixture is not higher than 10.

[0016] Preferably, the first constant temperature is no more than 100°C.

[0017] Preferably, the first constant temperature is 70-90°C.

[0018] Preferably, after the aluminosilicate stone tailings are crushed to obtain a rough processed product of the aluminosilicate stone tailings, the method further comprises the following steps:

[0019] The coarsely treated product is ground to pass through a 60-mesh sieve to obtain a ground treated product;

[0020] mixing the ground product with hydrochloric acid to obtain a first filtrate and a first precipitate;

[0021] mixing the first precipitate with sodium hydroxide and stirring to obtain a second mixture;

[0022] The first filtrate is mixed with sodium hydroxide of a second concentration until no precipitation is generated, and excess calcium hydroxide is added and filtered to obtain a second filtrate;

[0023] The second mixture and the second filtrate are mixed in a mass ratio of 1:5 to obtain a third mixture, and the third mixture, the first mixture, and at least one of 0.1 mol / L cyclohexanol and 0.1 mol / L 2-cyclohexene-1-ol are mixed to obtain an environmental remediation material.

[0024] The beneficial effects of the technical solution provided by this application include:

[0025] The present invention provides a method for preparing environmental restoration functional materials from tailings of stone mines. Since the aluminosilicate stone tailings are rich in silicon dioxide, aluminum oxide, etc., the particle size of the rough-treated product obtained after rough treatment is no more than 2 mm. After modification by sodium hydroxide, the ash content of the tailings particles is removed, and a large number of NaOH particles are attached to the surface of the tailings particles. The ionized OH - It can combine with positive ions in pollutants to form precipitation, thereby achieving the adsorption of heavy metal elements, making full use of the inherent components of aluminosilicate stone tailings;

[0026] During the slow heating process, the corrosion of the tailings particles by sodium hydroxide is further aggravated, the surface of the tailings particles becomes uneven, and the porosity is increased; after cooling, at least one of cyclohexanol and 2-cyclohexene-1-ol is added to modify the tailings particles to obtain an environmental remediation material with C=C double bonds and / or hydroxyl groups, which has good ion exchange properties and molecular adsorption characteristics. Therefore, the silicon and aluminum of the aluminosilicate stone tailings are effectively utilized, effectively solving the problem of insufficient utilization of stone tailings and easy pollution. The obtained environmental remediation material can be widely used in the treatment of heavy metal pollution and pollution remediation. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 A flow chart of the preparation of environmental remediation materials provided in the embodiments of the present application;

[0029] Figure 2 The environmental restoration materials prepared in Examples 1 to 4 provided in this application have a significant effect on Cd 2+ "Adsorption time-adsorption capacity" relationship diagram;

[0030] Figure 3 The environmental restoration materials prepared in Examples 4 to 6 provided in this application have a significant effect on Cd 2+ "Adsorption time-adsorption capacity" relationship diagram;

[0031] Figure 4 The environmental restoration material prepared in Example 5 provided in this application has a significant effect on Cd 2+ The relationship diagram of “environmental remediation material input-removal rate”. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0033] See also Figure 1-4 , the present invention provides a technical solution:

[0034] A method for preparing environmental restoration functional materials from stone mine tailings can solve the problem of insufficient utilization of stone tailings and easy environmental pollution in related technologies.

[0035] The present application provides a method for preparing environmental restoration functional materials from stone mine tailings, wherein the aluminosilicate stone tailings can be selected from rocks rich in aluminosilicate minerals such as feldspar, such as tailings produced by stone mining such as granite and sandstone. These rock tailings contain the main chemical components required for the formation of clay minerals, namely silicon and aluminum. The method provided in this embodiment includes the following steps:

[0036] S1. Broken.

[0037] Specifically, the aluminosilicate stone tailings are crushed to obtain a rough processed product, so that the particle size of the stone tailings is reduced, the surface area is increased, and it is convenient for subsequent processing. Further, the particle size of the rough processed product is not greater than 2mm.

[0038] S2. preparing a first mixture.

[0039] Specifically, the crude product is mixed with a sodium hydroxide solution and stirred for at least 0.5 h to obtain a first mixture. Since the aluminosilicate stone tailings contain silicon and aluminum elements, sodium silicate (Na2SiO3) and sodium aluminate (NaAlO2) will be generated by reacting with sodium hydroxide. Sodium silicate is a strong base and weak acid salt, and coexists with alkaline sodium aluminate in the first mixture. Hydroxide is suspended in the first mixture, and the hydroxide forms hydroxide precipitates with heavy metal ions, which reduces the content of heavy metals in water or soil and can reduce harm to the environment.

[0040] S3, heating the first mixture.

[0041] The first mixture is placed in a heating container, the heating container is heated from 10°C at a heating rate of 5°C / min, and maintained at a first constant temperature for 1.5 to 3 hours. Optionally, the first constant temperature can be selected to be 1.5 hours, 2 hours or 3 hours.

[0042] Specifically, the heating container can be a muffle furnace, and during the heating process, the temperature is increased at a certain rate so that the sodium silicate and sodium aluminate can respond fully and in time.

[0043] Optionally, the first constant temperature does not exceed 100°C.

[0044] Optionally, the first constant temperature is between 70°C and 90°C, preferably 90°C, and may also be 70°C or 80°C.

[0045] S4. Prepare environmental restoration materials.

[0046] The first mixture is cooled to no higher than 25° C., at least one of 0.1 mol / L of cyclohexanol and 0.1 mol / L of 2-cyclohexene-1-ol is added, and stirred for at least 20 minutes to obtain an environmental remediation material.

[0047] Optionally, the pH of the first mixture is not lower than 7 and not higher than 10, making the first mixture alkaline.

[0048] Environmental remediation materials as Cd 2+ The removed repair agent, specifically, Cd 2+ The solution can be prepared with deionized water and Cd(NO3)2 to prepare a Cd solution with a concentration of 10 mg / L. According to the volume of the Cd solution, 10 g / L is added to the Cd solution.

[0049] Example 1

[0050] The preparation method of the environmental restoration material of this embodiment is as follows:

[0051] S1. Crushing the aluminosilicate stone tailings to obtain a rough-processed aluminosilicate stone tailings, and making the particle size of the rough-processed aluminosilicate stone tailings be between 0.5 and 2 mm.

[0052] S2. Mix the crude product with a sodium hydroxide solution and stir for 1 h to obtain a first mixture.

[0053] S3. placing the first mixture in a muffle furnace, heating the muffle furnace from 10° C. at a heating rate of 5° C. / min, and maintaining the temperature at 90° C. for 2 h.

[0054] S4. Cool the first mixture to 25° C., add 0.1 mol / L cyclohexanol, with the mass ratio of cyclohexanol to the first mixture being 1:5, and stir for 30 minutes to obtain the environmental remediation material of this embodiment.

[0055] 50 mL of 10 mg / L Cd solution was measured, 0.5 g of the environmental remediation material prepared in this example was weighed, and the mixture was shaken on a shaker at 200 r / min at room temperature. Samples were taken at 0, 10, 20, 40, 80, 150, 300, 600, and 1200 minutes, and the residual Cd concentration was determined.

[0056] Combination Figure 2 As shown in the figure, with the increase of adsorption time, the adsorption gradually stabilizes. In the initial stage of adsorption, Cd 2+ The removal rate was faster and reached a steady state after 400 minutes.

[0057] Example 2

[0058] The preparation method of the environmental restoration material of this embodiment is as follows:

[0059] S1. Crushing the aluminosilicate stone tailings to obtain a rough-processed aluminosilicate stone tailings, and making the particle size of the rough-processed aluminosilicate stone tailings be between 0.5 and 2 mm.

[0060] S2. Mix the crude product with a sodium hydroxide solution and stir for 1 h to obtain a first mixture.

[0061] S3. placing the first mixture in a muffle furnace, heating the muffle furnace from 10° C. at a heating rate of 5° C. / min, and maintaining the temperature at 90° C. for 2 h.

[0062] S4. Cool the first mixture to 25° C., add 0.1 mol / L of 2-cyclohexene-1-ol, and the mass ratio of 2-cyclohexene-1-ol to the first mixture is 1:6, and stir for 30 minutes to obtain the environmental remediation material of this embodiment.

[0063] 50 mL of 10 mg / L Cd solution was measured, 0.5 g of the environmental remediation material prepared in this example was weighed, and the mixture was shaken on a shaker at 200 r / min at room temperature. Samples were taken at 0, 10, 20, 40, 80, 150, 300, 600, and 1200 minutes, and the residual Cd concentration was determined.

[0064] Combination Figure 2 As shown in the figure, with the increase of adsorption time, the adsorption gradually stabilizes. In the initial stage of adsorption, Cd 2+ The removal rate was fast and reached a steady state at about 400 minutes.

[0065] Example 3

[0066] The preparation method of the environmental restoration material of this embodiment is as follows:

[0067] S1. Crushing the aluminosilicate stone tailings to obtain a rough-processed aluminosilicate stone tailings, and making the particle size of the rough-processed aluminosilicate stone tailings be between 0.5 and 2 mm.

[0068] S2. Mix the crude product with a sodium hydroxide solution and stir for 1 h to obtain a first mixture.

[0069] S3. placing the first mixture in a muffle furnace, heating the muffle furnace from 10° C. at a heating rate of 5° C. / min, and maintaining the temperature at 90° C. for 2 h.

[0070] S4. Cool the first mixture to 25°C, add 0.1 mol / L cyclohexanol and 0.1 mol / L 2-cyclohexene-1-ol, and the mass ratio of cyclohexanol to the first mixture is 1:5, and the mass ratio of 2-cyclohexene-1-ol to the first mixture is 1:6, and stir for 30 minutes to obtain the environmental remediation material of this embodiment.

[0071] 50 mL of 10 mg / L Cd solution was measured, 0.5 g of the environmental remediation material prepared in this example was weighed, and the mixture was shaken on a shaker at 200 r / min at room temperature. Samples were taken at 0, 10, 20, 40, 80, 150, 300, 600, and 1200 minutes, and the residual Cd concentration was determined.

[0072] Combination Figure 2 As shown in the figure, with the increase of adsorption time, the adsorption gradually stabilizes. In the initial stage of adsorption, Cd 2+ The removal rate was fast and reached a steady state at about 400 minutes.

[0073] Example 4

[0074] The preparation method of the environmental restoration material of this embodiment is as follows:

[0075] S1. Crushing the aluminosilicate stone tailings to obtain a rough-processed aluminosilicate stone tailings, and making the particle size of the rough-processed aluminosilicate stone tailings be between 0.5 and 2 mm.

[0076] S2. Mix the crude product with a sodium hydroxide solution and stir for 1 h to obtain a first mixture.

[0077] S3, grinding the coarsely treated product until it passes through a 60-mesh sieve to obtain a ground treated product.

[0078] S4, mixing the ground product with hydrochloric acid to obtain a first filtrate and a first precipitate.

[0079] S5. Mix the first filtrate with sodium hydroxide of a second concentration until no more precipitation is generated, add excess calcium hydroxide, and filter to obtain a second filtrate.

[0080] S6. placing the first mixture in a muffle furnace, heating the muffle furnace from 10° C. at a heating rate of 5° C. / min, and maintaining the temperature at 90° C. for 2 h.

[0081] S7. Cool the first mixture to 25°C, mix the second mixture and the second filtrate in a mass ratio of 1:5 to form a third mixture, mix the third mixture and the cooled first mixture with 0.1 mol / L cyclohexanol (wherein the mass ratio of the third mixture to the first mixture is 1:1, and the mass ratio of cyclohexanol to the first mixture is 1:5), to obtain the environmental remediation material of this embodiment.

[0082] 50 mL of 10 mg / L Cd solution was measured, 0.5 g of the environmental remediation material prepared in this example was weighed, and the mixture was shaken on a shaker at 200 r / min at room temperature. Samples were taken at 0, 10, 20, 40, 80, 150, 300, 600, and 1200 minutes, and the residual Cd concentration was determined.

[0083] Combination Figure 2 As shown in the figure, with the increase of adsorption time, the adsorption gradually stabilizes. In the initial stage of adsorption, Cd 2+ The removal rate was fast and reached a steady state at about 400 minutes.

[0084] Comparative Example

[0085] The preparation method of the environmental restoration material of this embodiment is as follows:

[0086] (1) The aluminosilicate stone tailings are crushed to obtain a rough-treated aluminosilicate stone tailings, and the particle size of the rough-treated aluminosilicate stone tailings is set at 0.5-2 mm. The tailings particles that have not been treated with reagents such as sodium hydroxide are used as a comparative example of environmental remediation materials.

[0087] 50 mL of 10 mg / L Cd solution was measured, 0.5 g of the environmental remediation material prepared in this example was weighed, and the mixture was shaken on a shaker at 200 r / min at room temperature. Samples were taken at 0, 10, 20, 40, 80, 150, 300, 600, and 1200 minutes, and the residual Cd concentration was determined.

[0088] pass Figure 2 It can be seen that the environmental remediation materials prepared in Examples 1 to 4 of the present application have a significant effect on Cd 2+ The adsorption effect of the crushed particles of aluminum silicate stone tailings on Cd was significantly higher than that of the crushed particles of aluminum silicate stone tailings in the comparative example.2+ In addition, the environmental remediation material prepared in Example 4 has a better adsorption effect and a larger adsorption capacity than those in Examples 1 to 3.

[0089] The difference between Example 4 and Examples 1 to 3 is that the rough treated product obtained in step S1 is ground again, which includes the following steps:

[0090] S101, grinding the roughly treated product obtained in step S1 until it passes through a 60-mesh sieve to obtain a ground treated product;

[0091] S102, mixing the ground product with hydrochloric acid to obtain a first filtrate and a first precipitate, wherein the hydrochloric acid can be a hydrochloric acid solution with a concentration of 0.1 mol / L;

[0092] S103, mixing the first precipitate with sodium hydroxide and stirring to obtain a second mixture, wherein the sodium hydroxide here can be a sodium hydroxide solution with a concentration of 0.1 mol / L;

[0093] S104, the first filtrate is mixed with sodium hydroxide until no precipitation is generated, excess calcium hydroxide is added, and the mixture is filtered to obtain a second filtrate. Optionally, the sodium hydroxide here can be a sodium hydroxide solution with a concentration of 0.1 mol / L;

[0094] S105. Mix the second mixture and the second filtrate in a mass ratio of 1:5 to obtain a third mixture, and mix the third mixture, the first mixture, and at least one of 0.1 mol / L cyclohexanol and 0.1 mol / L 2-cyclohexene-1-ol to obtain an environmental remediation material.

[0095] Among them, the purpose of the grinding treatment is to make the particle size of the stone tailings particles smaller. After the ground product is mixed with hydrochloric acid, the calcium carbonate and iron oxide that may exist in the stone tailings will react to form calcium chloride and iron chloride (the first filtrate), remove a part of the possible impurities, and separate the silicon dioxide (the first precipitate). The silicon dioxide reacts with sodium hydroxide to form sodium silicate (the second mixture). The second filtrate in step S104 is sodium aluminate. The second mixture (sodium silicate) and the second filtrate (sodium aluminate) are mixed in a mass ratio of 1:5 to obtain a third mixture with better adsorption of heavy metal ions.

[0096] Specifically, silicon in aluminosilicate stones mostly exists in the form of SiO2 (silicon dioxide), and aluminum mostly exists in the form of Al2O3 (aluminum oxide). Taking granite as an example, the components of granite include minerals such as quartz or feldspar. According to the average proportion of different chemical components in 2485 granites from all over the world, in terms of weight percentage from heavy to light, they are SiO2 (72.04%) and Al2O3 (14.42%). Therefore, in this embodiment, the second mixture (sodium silicate) and the second filtrate (sodium metaaluminate) are mixed in a mass ratio of 1:5, so that the ratio with silicon is close to or reaches 1:1, and a third mixture is obtained.

[0097] Combination Figure 2 As shown, after the third mixture and the first mixture are mixed with 0.1 mol / L cyclohexanol, the heavy metal adsorption capacity of the environmental restoration material obtained is better than the heavy metal adsorption capacity of the environmental restoration material without adding the third mixture.

[0098] Optionally, in Example 4, the cyclohexanol added in step (7) can also be replaced by 2-cyclohexene-1-ol, or a mixture of the two. When 2-cyclohexene-1-ol replaces cyclohexanol, the mass ratio of 2-cyclohexene-1-ol to the first mixture is 1:6; when a mixture of the two is added, the mass ratio of cyclohexanol to the first mixture is 1:5, and the mass ratio of 2-cyclohexene-1-ol to the first mixture is 1:6.

[0099] Preferably, in Example 4, a mixture of cyclohexanol and 2-cyclohexene-1-ol is added in step (7) to further modify the environmental remediation material, so that the groups on the surface of the tailings particles, such as hydroxyl groups, react with Cd for precipitation, and introduce C=C bonds, so that Cd-π plays an important role in the adsorption effect.

[0100] Furthermore, the powdered stone tailings after grinding can be sieved, and the powder after grinding can be sieved through sieves with different apertures to separate particles of different sizes for subsequent processing. Preferably, the aluminosilicate stone tailings powder is sieved through a 60-mesh sieve so that it can fully react with the reagent during subsequent chemical treatment to form a better environmental remediation material.

[0101] Example 5

[0102] The preparation method of the environmental restoration material of this embodiment is as follows:

[0103] S1. Crushing the aluminosilicate stone tailings to obtain a rough-processed aluminosilicate stone tailings, and making the particle size of the rough-processed aluminosilicate stone tailings be between 0.5 and 2 mm.

[0104] S2. Mixing the crude product with a sodium hydroxide solution and stirring for 0.5 h, wherein the concentration of the sodium hydroxide solution is 45%, to obtain a first mixture, and the pH of the first mixture is 8.

[0105] S3, grinding the coarsely treated product until it passes through a 60-mesh sieve to obtain a ground treated product.

[0106] S4, mixing the ground product with hydrochloric acid to obtain a first filtrate and a first precipitate.

[0107] S5. Mix the first filtrate with sodium hydroxide of a second concentration until no more precipitation is generated, add excess calcium hydroxide, and filter to obtain a second filtrate.

[0108] S6. placing the first mixture in a muffle furnace, heating the muffle furnace from 10° C. at a heating rate of 5° C. / min, and maintaining the temperature at 90° C. for 2 h.

[0109] S7. Cool the first mixture to no higher than 25°C, mix the second mixture and the second filtrate in a mass ratio of 1:5 to form a third mixture, mix the third mixture and the cooled first mixture with 0.1 mol / L cyclohexanol (wherein the mass ratio of the third mixture to the first mixture is 1:1, and the mass ratio of cyclohexanol to the first mixture is 1:5), to obtain the environmental remediation material of this embodiment.

[0110] 50 mL of 10 mg / L Cd solution was measured, 0.5 g of the environmental remediation material prepared in this example was weighed, and the mixture was shaken on a shaker at 200 r / min at room temperature. Samples were taken at 0, 10, 20, 40, 80, 150, 300, 600, and 1200 minutes, and the residual Cd concentration was determined.

[0111] See also Figure 3 As shown in the figure, it can be seen that the environmental restoration material prepared in Example 5 has a significant effect on Cd 2+ The repair effect is higher than that of the environmental repair material prepared in Example 4, and specifically, the environmental repair material prepared in Example 5 has a better adsorption effect and a larger adsorption capacity.

[0112] Example 6

[0113] The preparation method of the environmental restoration material of this embodiment is as follows:

[0114] S1. Crushing the aluminosilicate stone tailings to obtain a rough-processed aluminosilicate stone tailings, and making the particle size of the rough-processed aluminosilicate stone tailings be between 0.5 and 2 mm.

[0115] S2. Mixing the crude product with a sodium hydroxide solution and stirring for 0.5 h, wherein the concentration of the sodium hydroxide solution is 45%, to obtain a first mixture, and the pH of the first mixture is 8.

[0116] S3, grinding the coarsely treated product until it passes through a 60-mesh sieve to obtain a ground treated product.

[0117] S4, mixing the ground product with hydrochloric acid to obtain a first filtrate and a first precipitate.

[0118] S5. Mix the first filtrate with sodium hydroxide of a second concentration until no more precipitation is generated, add excess calcium hydroxide, and filter to obtain a second filtrate.

[0119] S6. placing the first mixture in a muffle furnace, heating the muffle furnace from 10° C. at a heating rate of 5° C. / min, and maintaining the temperature at 90° C. for 2 h.

[0120] S7. Cool the first mixture to 25°C, mix the second mixture and the second filtrate in a mass ratio of 1:5 to form a third mixture, mix the third mixture and the cooled first mixture with 0.1 mol / L cyclohexanol and 0.1 mol / L 2-cyclohexene-1-ol (wherein the mass ratio of the third mixture to the first mixture is 1:1, the mass ratio of cyclohexanol to the first mixture is 1:5, and the mass ratio of 2-cyclohexene-1-ol to the first mixture is 1:6), to obtain the environmental remediation material of this embodiment.

[0121] 50 mL of 10 mg / L Cd solution was measured, 0.5 g of the environmental remediation material prepared in this example was weighed, and the mixture was shaken on a shaker at 200 r / min at room temperature. Samples were taken at 0, 10, 20, 40, 80, 150, 300, 600, and 1200 minutes, and the residual Cd concentration was determined.

[0122] See also Figure 3 As shown in the figure, it can be seen that the environmental restoration material prepared in Example 6 has a significant effect on Cd 2+ The repair effect is higher than that of the environmental repair material prepared in Example 4, but lower than that of the environmental repair material prepared in Example 5. This may be due to the poor performance of 2-cyclohexene-1-ol in the third mixture.

[0123] Specifically, aluminosilicate stone tailings contain a small amount of Fe, which can react with concentrated sodium hydroxide solution to generate sodium ferrite NaFeO2; on the one hand, concentrated sodium hydroxide reacts with iron to generate sodium ferrite NaFeO2, and on the other hand, the environmental remediation material prepared after the tailings particles are modified with high concentration NaOH has an increased adsorption capacity, and the alkaline group -OH reacts with Cd to precipitate, which is beneficial to the adsorption of Cd, that is, under alkaline conditions, the environmental remediation material prepared has a better adsorption effect.

[0124] Furthermore, the pH value of the first mixture can be adjusted to 7-10, thereby making the environmental remediation material alkaline. When the pH of the environmental remediation material is low, there are more hydrogen ions in the solution, the dissociation effect of the hydroxyl groups in the environmental remediation material is poor, the effective active centers are occupied by hydrogen ions, and there are no adsorption sites for heavy metal ions, so the adsorption efficiency is low; as the pH of the solution increases, the hydroxyl groups dissociate, a large number of active centers are exposed, and Cd 2+ It is adsorbed on the active center, and the adsorption rate increases. Therefore, the environmental remediation material is more sensitive to Cd 2+ The adsorption capacity increases with the increase of pH.

[0125] Furthermore, under alkaline conditions (high pH), the hydroxyl groups on the surface of silicate (sodium silicate) particles may be deprotonated, which enhances their ion exchange activity. At the same time, the chemical behavior of heavy metal ions in an alkaline environment will also change, such as the formation of hydroxide precipitation, thereby achieving a better effect of removing heavy metal ions from water.

[0126] Test Case

[0127] The environmental remediation material obtained in Example 5 was added into 50 mL of 10 mg / mL Cd solution at a dosage of 5 g / L, 8 g / L, 10 g / L, 15 g / L, 18 g / L, and 20 g / L, respectively, and shaken at room temperature at a speed of 200 r / min. After reacting for 400 min, the supernatant was taken, the residual Cd concentration was determined, and the removal rate was calculated. The results are shown in Figure 4 .Depend on Figure 4 It can be seen that under this treatment condition, with the increase of the amount of environmental remediation materials added, the 2+ The removal rate of Cd also increased. When the dosage increased to 15 g / L, 2+ The adsorption effect of Cd 2+ The removal rate can reach up to 79.1%.

[0128] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing environmental restoration functional materials from stone mine tailings, characterized in that: It includes the following steps: The aluminum silicate stone tailings are crushed to obtain a rough-processed product of the aluminum silicate stone tailings, wherein the particle size of the rough-processed product is not greater than 2 mm; The crude product is mixed with a sodium hydroxide solution and stirred for at least 0.5 h to obtain a first mixture, wherein the concentration of the sodium hydroxide solution is greater than 40%; Placing the first mixture in a heating container, heating the heating container from 10° C. at a heating rate of 5° C. / min, and maintaining the first constant temperature for 1.5 to 3 hours, wherein the first constant temperature is no more than 100° C.; Grinding the coarsely treated product until it passes through a 60-mesh sieve to obtain a ground treated product; mixing the ground product with hydrochloric acid to obtain a first filtrate and a first precipitate; The first precipitate is mixed with a sodium hydroxide solution and stirred to obtain a second mixture, wherein the concentration of the sodium hydroxide solution is 0.1 mol / L; The first filtrate is mixed with a sodium hydroxide solution until no precipitation is generated, and excess calcium hydroxide is added and filtered to obtain a second filtrate, wherein the concentration of the sodium hydroxide solution is 0.1 mol / L; Cooling the first mixture to no higher than 25° C., and mixing the second mixture with the second filtrate at a mass ratio of 1:5 to obtain a third mixture; The third mixture and the first mixture are mixed with at least one of 0.1 mol / L of cyclohexanol or 0.1 mol / L of 2-cyclohexene-1-ol, and stirred for at least 20 minutes to obtain an environmental remediation material.

2. The method for preparing environmental restoration functional materials from stone mine tailings according to claim 1, characterized in that: When preparing the first mixture, the sodium hydroxide solution is added in excess, and the pH value of the first mixture is not less than 7.

3. The method for preparing environmental restoration functional materials from stone mine tailings as claimed in claim 2, characterized in that: The pH value of the first mixture is not higher than 10.

4. The method for preparing environmental restoration functional materials from stone mine tailings according to claim 1, characterized in that: The first constant temperature is 70-90°C.

Citation Information

Patent Citations

  • Nanocrystal material based on steric hindrance regulation and preparation method thereof

    CN115432712A

  • Ionic rare earth tailing-based zeolite material and method for removing lead ions in solution by using ionic rare earth tailing-based zeolite material

    CN117105241A